Dynamics of molten pool evolution and high-speed real-time optical measurement in laser polishing - Du Wang; Mingjie Yu; Yifan Yao; Shaoyi Wang; Yueyun Weng; Shuang Zhao; Fei Fan; Keisuke Goda; Sheng Liu; Zongqing Zhao; Cheng Lei (Light: Advanced Manufacturing)
Laser polishing (LP) is considered an effective method for generating ultrasmooth surfaces owing to its precision, flexibility, and material compatibility. However, a lack of understanding of the evolution of surface topography during LP significantly limits the achievable surface roughness in practice. In this work, for the first time, by employing optical time-stretch quantitative interferometry (OTS-QI), we recorded the entire evolution of surface topography during LP with nanosecond-level temporal resolution, providing insight into the mechanisms involved in the surface roughness evolution, such as the Marangoni effect and the formation mechanism of mid-frequency waviness (MFW). Assisted by numerical calculations, we reveal that a ‘perfect polishing point’ exists, i.e., the optimal interaction time for LP at a specific laser power density, at which the surface roughness can be minimised without the formation of an MFW owing to the Marangoni effect and non-uniform removal. This OTS-QI system harnesses the rapid repetition rate of femtosecond lasers, achieving a remarkable measurement speed exceeding 100,000,000 times per second while preserving a measurement accuracy comparable to that of existing white light interferometers (WLIs), setting a new benchmark as the fastest recorded roughness measurement. In addition to LP, the proposed method can be applied for real-time and in situ monitoring of many machining scenarios involving highly dynamic phenomena.